Building Ethereum Dapps : decentralized applications on the Ethereum blockchain - Infante, Roberto (Manning Publications, 2019)
Imagine unbreakably secure applications that handle personal and business transactions without any central agency controlling the process. Decentralized applications, or Dapps, do just this, shifting power to users. The Ethereum blockchain platform provides the tools you need to build Dapps, including an innovative "smart contracts" model and solidity, a Dapp-aware JavaScript-like programming language. "Building Ethereum Dapps" teaches Dapps development on the Ethereum blockchain platform. You'll begin with a mental model of how Dapps operate, and then dive into designing and implementing smart contracts in Ethereum's Solidity language. You'll explore Ethereum smart contract development tools, like Truffle and Web3, and pick up best practices for design and security. Practical exercises throughout give you valuable hands-on experience